Exploration of development inequality models in north Sumatera - Armin Rahmansyah Nasution; Ainul Mardhiyah; Muammar Rinaldi (Trigin Publisher, 2025)
Development disparities are essentially economic disparities, which imply poverty and inequality. In order to prevent the gap between one region and another from widening further, policy implications for the development cycle must be formulated accurately. This study aims to analyze the factors that influence development disparities among regencies/cities in North Sumatra Province. The data used in this study are secondary time series data from 2013 to 2024, obtained from the Central Bureau of Statistics (BPS) of North Sumatra. The research method employs panel data analysis using a fixed effect model approach. Research Results show that an increase in GRDP per capita, the quality of human resources through the Human Development Index (HDI), and infrastructure development collectively contribute to reducing regional development disparities. Policy implications of this study highlight the need for inclusive economic growth that ensures a fair distribution of development benefits across all regions and economic sectors.